2009
DOI: 10.1590/s1808-86942009000500024
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in cochlear function during induced acute hyperinsulinemia in an animal model

Abstract: Hyperi nsulinism secondary to peripheral insulin resistance has been described as the most frequent etiologic factor in cochlear and vestibular syndromes. Aim: This experimental study recorded and analyzed evoked auditory potential changes using transtympanic electrocochleography (EcochG) during induced acute hyperinsulinism in an animal model. Materials and Methods: Six adult male sheep were randomly divided into 2 groups. The animals were submitted to EcochG under general anesthesia, and a peripheral blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Changes in glucose metabolism have been associated with a high prevalence of inner ear disorders, hence with BPPV occurrence and recurrence [ 14 , 49 , 50 ]. These metabolic disorders can act as a principal etiologic factor in vestibular dysfunction, as well as an aggravating factor of a pre-existing vestibular disorder [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in glucose metabolism have been associated with a high prevalence of inner ear disorders, hence with BPPV occurrence and recurrence [ 14 , 49 , 50 ]. These metabolic disorders can act as a principal etiologic factor in vestibular dysfunction, as well as an aggravating factor of a pre-existing vestibular disorder [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these patients present mutations in the BETA2/NeuroD1 gene which is essential for the normal development of the sensory epithelia of the cochlea, utricle, saccule, and crista ampullaris [ 53 ]. On the other hand, hyperinsulinism may disrupt inner ear homeostasis and alter the ionic and metabolic characteristics of the stria vascularis, which is responsible for maintaining endocochlear potential through potassium secretion in the endolymphatic space [ 49 , 51 ]. The inner ear is also affected by hyperinsulinism due to a large number of the insulin receptors present in the endolymphatic sac [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that the stria is the site of intense metabolic activity in the labyrinth. 35,36 A study revealed vestibular caloric stimulation (CS) inhibited noradrenergic (NA) neurons of the locus coeruleus (LC) in rats and hence speculating that LC-NA inhibition participates in the development of sensory mismatch during vertigo and motion sickness. 37 In diabetes mellitus, the observed changes are microangiopathy and peripheral neuropathy with consequent terminal blood flow problems and irregular supply of glucose.…”
Section: Discussionmentioning
confidence: 99%
“…A tone burst stimulus was delivered at the external acoustic meatus in frequencies ranging between 4200-6820 Hz and intensity of 82 SPL, according to the protocol of electrophysiological threshold recording of normal cochlear potentials in sheep 5 .…”
Section: Recording Of Auditory Evoked Potentialsmentioning
confidence: 99%